Fitrah-Based Sexuality Education for Early Childhood: An Islamic Education Perspective on Identity Development - Pragita, Faizah Dani; Surawan, Surawan; Norhidayah, Siti; Zahra, Fathimatuz (Universitas Muhammadiyah Yogyakarta, 2026)
Early childhood is a critical period for identity formation, including the development of self-concept and gender awareness. In Islamic education, the concept of fitrah provides a foundational framework for holistic human development aligned with divine values. However, sexuality education for young children is often avoided or misunderstood, resulting in limited ethical and educational guidance during this formative stage. This condition highlights the need for a value-based educational approach grounded in Islamic principles. This study aims to explore fitrah-based sexuality education as an Islamic educational approach to strengthening identity development in early childhood. Employing a qualitative library research method, the study analyses classical Islamic texts, contemporary scholarly literature, and relevant studies on child development, sexuality education, and Islamic ethics. The findings indicate that fitrah-based sexuality education emphasizes the integration of cognitive, emotional, spiritual, and social dimensions in nurturing children’s identity in accordance with their innate nature as male or female. Parents play a central role as primary educators by providing age-appropriate guidance, positive role modelling, and moral value internalization. Furthermore, the effectiveness of this approach is strengthened through the support of educational institutions, government policies, and social environments responsive to children’s developmental needs. The originality of this study lies in its conceptual synthesis of fitrah theory and early childhood sexuality education, reframing the discourse from a problem-oriented perspective to a constructive framework focused on identity strengthening and ethical development. This study recommends integrating fitrah-based sexuality education into family education practices and early childhood education programs.